Предмет: Математика,
автор: Аноним
3 + 2 [x − 2[x + 2(x−2)]] − 1 = 4
Ответы
Автор ответа:
2
3 + 2 [x − 2[x + 2(x−2)]] − 1 = 4,
3 + 2 [x − 2[x + 2x − 4]] − 1 = 4,
3 + 2 [x − 2x - 4x + 8] − 1 = 4,
3 + 2 [8 - 5х] − 1 = 4,
3 + 16 - 10х - 1 = 4,
-10х = 4 - 3 - 16 + 1,
-10х = -14,
х = 1,4
Похожие вопросы
Предмет: Английский язык,
автор: 070304Masha
Предмет: Алгебра,
автор: arnatalgatovna
Предмет: Русский язык,
автор: virskiy
Предмет: Информатика,
автор: 159135
Предмет: Литература,
автор: LolKekCheburek228133